The Effect of Solar and Lunar Attraction and SRP on the HEO of Satellite - H. Salah, Abdulrahman; Musa Murad, Ismail (Iraqi Journal of Science, 2023)
The perturbation of a satellite high orbit due to the presence of othergravitational bodies (such as the Sun and the Moon) and SRP from the conservativeperturbing forces were studied, using our modified model. A precise calculation ofthe perturbations is possible only if the initial orbit is sufficiently well known.Orbital elements that have been entered hp=3000Km., inclination= 63ᵒ, 23ᵒ andeccentricity= 0.1, longitude of ascending node 30ᵒ, argument of perigee 40ᵒ wherethe orbital elements will deviate from initial values with time through 3000 days.Newton-Rapson method was used to calculate the position and velocity with outperturbation . The perturbed equation of motion solved numerically using the fourthorder Runge-Kutta method .The results appear that all elements are varies nonlinear with time for all inclination 63,23 deg ,the time period was increased, It’smean value 22.55 hours with i=63ᵒ and 22.52 hours with i=23ᵒ deg. and the orbitapproach to circle .